The Effect of High-Temperature Heat Treatment on the Precipitation Behavior and Mechanical Properties of Mg-Al-Zn-Ca Alloys - Yan, Tian; Du, Tengfei (Scientific Journal of Technology, 2025)
This study first involves the melting of Mg-xAl-(8-x)Zn-(2-3)Ca (wt%, where unspecified refers to weight percentage) magnesium alloys with various compositions. The microstructure of the alloys is investigated using techniques such as OM, SEM, and XRD. It is found that variations in the Al/Zn ratio and Ca content significantly affect the composition and quantity of the second phase within the Mg-Al-Zn-Ca alloy system. Through tensile tests on five different alloys, it is observed that the Mg-3Al-5Zn-3Ca alloy exhibits relatively good comprehensive mechanical properties, achieving a tensile strength, yield strength, and elongation of 149 MPa, 99 MPa, and 3.1%, respectively. The precipitation behavior of the five alloys is studied, revealing that the Mg-3Al-5Zn-3Ca alloy, when heat-treated at 350℃ for 60 hours, precipitates a high-density rod-like phase with a density of approximately 0.14N/μm² and an average size of 1.21μm. Under the influence of precipitation strengthening, the comprehensive mechanical properties of the alloy are enhanced.